Prospects of Foresight in Russia are Unlimited - Yaroslav Kuzminov (Foresight and STI Governance)
Yaroslav Kuzminov, rector of the State University - Higher School of Economics Prospects, discusses the prospects of Foresight’s development in Russia and tells on the activity of the HSE International Academic and Research Foresight Centre.